Japan’s Giga School Program: Equips Students with Life Skills for Digital - Adriani, Sri Dewi (Daengku: Journal of Humanities and Social Sciences Innovation, 2025)
The Covid 19 pandemic is a human tragedy impacting all life aspects. One of them is education. In Japan, several policies were implemented to address gaps in access to education due to school closures during the pandemic. This article aims to describe the policy of the Japanese government in building a distance learning system that can be accessed equally by all students. This policy is known as The Global and Innovation Gateway for All (GIGA)'s school program. This program carries the concept of "one student, one device.” The method used in this research is document analysis (documentary analysis method) on several reports issued by related ministries and statistical data. From the study results, it can be concluded that this policy successfully reduced the gaps in accessing distance education while creating a new, modern civilization in the teaching process in educational environments in Japan.